IFN-γ/Doxorubicin Complex Nanoparticles for Enhancing Therapy in the Context of Human Ovarian Carcinoma - Yi, Rongyuan; Lv, Wanwan; Zheng, Shan; Zhang, Ningyu; Zhang, Yuheng; Yang, Kai; Huang, Tuo; Yang, Yanning; Chu, Hui; Chen, Jian (Frontiers in Materials, 2022)
The cytokine interferon gamma (IFN-γ) and doxorubicin mono-therapy has been approved by the Food and Drug Administration (FDA) for the treatment of anti-tumor. The importance of IFN-γ in the immune system lies in its immunomodulatory effects and the importance of doxorubicin in anti-tumor therapy lies in inhibiting RNS and DNA synthesis. In this work, the role of IFN-γ on the antitumor activity in combination with doxorubicin was investigated. Meanwhile, IFN-γ was used as vehicle to load doxorubicin over immunotherapy and chemotherapy for synergistic therapy. IFN-γ/doxorubicin complex nanoparticles were prepared by a fusion method with a size of approximately 13 nm and a low polydispersity index. The doxorubicin release profile was analyzed with different pH and it showed an enhanced release in acidic pH. The ability of IFN-γ/doxorubicin complex nanoparticles to induce human ovarian carcinoma cells (Skov 3) apoptosis was evaluated by cytotoxicity test. The cellular uptake of the IFN-γ/doxorubicin complex nanoparticles was time-dependent and the IFN-γ/doxorubicin complex nanoparticles showed a higher apoptosis efficiency than free doxorubicin by ﬂow cytometry analysis and ﬂuorescence imaging. This work bridged IFN-γ with doxorubicin to utilize their potential for antitumor, opening new avenues for their use in clinical settings.